2016
DOI: 10.1007/s10339-016-0787-0
|View full text |Cite
|
Sign up to set email alerts
|

Auditory preference of children with autism spectrum disorders

Abstract: Research on children with Autism Spectrum Disorders suggests differences from neurotypical children in the preference for ‘social’ versus ‘nonsocial’ sounds. Conclusions have been based largely on the use of head-turn methodology which has various limitations as a means of establishing auditory preference. In the present study, preference was assessed by measuring the frequency with which children pressed a button to hear different sounds using an interactive toy. Contrary to prior results, both groups display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In this set of tasks, the effort expended to prolong / increase exposure to social stimuli is used to index social seeking. For example, participants are presented a stimulus briefly and they are expected to make multiple/ quick button presses to increase the duration that a stimulus is presented for, or the amount of it that is presented (Ewing et al, 2013;Gilbertson et al, 2017;. An example of an expenditure task is presented in Figure 2c.…”
Section: Expenditure Tasksmentioning
confidence: 99%
“…In this set of tasks, the effort expended to prolong / increase exposure to social stimuli is used to index social seeking. For example, participants are presented a stimulus briefly and they are expected to make multiple/ quick button presses to increase the duration that a stimulus is presented for, or the amount of it that is presented (Ewing et al, 2013;Gilbertson et al, 2017;. An example of an expenditure task is presented in Figure 2c.…”
Section: Expenditure Tasksmentioning
confidence: 99%
“…Third, the method used to obtain an objective measure of relative preference for social sounds was the observation of eye-gaze or head-turn toward the person/agent giving the social bid. Though this “head-turn method” has been the most common means to investigate the attention to sound (Gilbertson et al 2016 ), it relies heavily on the assumption of a strong association between preference and orientation to a sound, when in fact the child’s attention to the social sound may be provoked for a variety of reasons unrelated to preference (e.g., distraction, surprise, or even annoyance) (Gilbertson et al 2016 ). Again, observation over multiple sessions with a variety of social presses may help further support sustained preference versus short-range attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the empirical studies testing the predictions of the social motivation theory have yielded mixed results. While some published works report that ASC is related to hypo-responsiveness specifically to social (e.g., Scott-Van Zeeland et al, 2010;Sepeta et al, 2012;Stavropoulos & Carver, 2014b, 2014a or both social and nonsocial rewards (e.g., Baumeister et al, 2020;Kohls et al, 2011Kohls et al, , 2013Kohls, Thönessen, et al, 2014;Richey et al, 2014), other studies found no differences between ASC and comparison groups (e.g., Demurie et al, 2016;Ewing et al, 2013;Gilbertson et al, 2017). Moreover, some studies reported hyper-responsiveness to rewards in ASC, especially to objects related to special interests (e.g., Cascio et al, 2014;Kohls et al, 2018;Watson et al, 2015), but also to other social and non-social rewards (e.g., Matyjek, Bayer, et al, 2020;Pankert et al, 2014;van Dongen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%